Revitalisasi Perpustakaan dan Peningkatan Literasi di SMPN 2 Kalibawang: Pengabdian melalui Program Kampus Mengajar - Zaki, Muhamad; Khoiri, Ahmad; Mutmainah, Kurniawati; Khanifa, Nurma Khusna (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Primary education plays a vital role in shaping students' character, literacy, and skills. However, limited literacy facilities pose a challenge at SMPN 2 Kalibawang. Therefore, there is a need for programs to support the creation of facilities that encourage students to have good literacy and numeracy. Objective: The purpose of this service is to optimize student literacy, interest in student creativity through strengthening literacy and numeracy at SMPN 2 Kalibawang through the Teaching Campus program while upholding Islamic values in the school. Method: This community service activity is carried out from September to December 2024 through collaborative activities with teachers and school organizations, including creating reading corners, literacy and numeracy games through Bamboozone, basic computer and Canva workshops, learning with interactive PPTs, creative classroom projects, and environmental literacy programs. The participants are 8th and 9th-grade students, teachers, and the wider school community. Result: This program successfully revitalized the library, improved student literacy through regular visits to the library, introduced basic computer skills and Canva, updated classroom bulletin boards with student creations, introduced technology as a learning tool, and enhanced numeracy understanding through interactive media. Students showed an increased interest in books, leading to continual improvements in their literacy and numeracy skills. Conclusion: The Campus Teaching Program makes a significant contribution to improving literacy and numeracy of students at SMPN 2 Kalibawang Wonosobo as a bridge to enhance the capabilities of the nation's youth in terms of knowledge and skills for a more advanced nation. Sustainable collaboration between students, teachers, and the Campus Teaching team is crucial for long-term improvement in the quality of education, thus continuity from teachers and increased awareness from students are necessary.